2004
DOI: 10.1099/vir.0.80246-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of putative atypical scrapie in sheep in Portugal

Abstract: Experimental transmission of bovine spongiform encephalopathy to sheep has prompted the implementation of a surveillance plan of scrapie in small ruminants by the European Union in all member states. Since its start over 30 000 animals have been tested, and the first seven cases of sheep with detectable PrP res deposition in the central nervous system have been identified in Portugal. Notably, the pattern of PrP res distribution in the brainstem was different from that previously described for scrapie and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 20 publications
6
71
0
2
Order By: Relevance
“…In the brainstem, some cases have been described as totally negative at the level of the obex [5,9,10,16,32] while other cases display minimal staining restricted only to the spinal tract nucleus of the trigeminal nerve [5,31,33,37,41]. The primary structure affected in classical scrapie, the dorsal motor nucleus of the vagus (DMNV) was never affected.…”
Section: Atypical/nor98 Scrapie Brains Have a Different Appearance Anmentioning
confidence: 99%
See 3 more Smart Citations
“…In the brainstem, some cases have been described as totally negative at the level of the obex [5,9,10,16,32] while other cases display minimal staining restricted only to the spinal tract nucleus of the trigeminal nerve [5,31,33,37,41]. The primary structure affected in classical scrapie, the dorsal motor nucleus of the vagus (DMNV) was never affected.…”
Section: Atypical/nor98 Scrapie Brains Have a Different Appearance Anmentioning
confidence: 99%
“…Evidence so far indicates that atypical scrapie affects animals with PrP genotypes different from classical scrapie [2,3,9,26,27,29,30,33,36]. The appearance of atypical/Nor98 scrapie and classical scrapie in the same flock has not been reported as a common event, although there is no apparent genetic reason for this: indeed the separation of susceptible genotypes would perfectly permit infection with both diseases in an infected flock.…”
Section: Association Of Prp Genetics With Atypical Scrapiementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, confirmatory neuropathological methods were often inconclusive [18]. Atypical scrapie has been diagnosed in sheep carrying various PrP genotypes, including those homozygous for ARR [40,137,141] Analyses of brain PrP res from natural scrapie cases revealed that scrapie molecular features are not uniform, consistent with the existence of distinct strains. Three major types of PrP res profiles have been identified, with unglycosylated forms (see Fig.…”
mentioning
confidence: 99%